On-Call Service of Neurosurgeons in Germany: Organization, Use of Communication Services, and Personal Acceptance of Modern Technologies - Brenke, Christopher; Lassel, Elke A.; Terris, Darcey; Kurt, Aysel; Schmieder, Kirsten; Schoenberg, Stefan O.; Weisser, Gerald (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background A significant proportion of acute care neurosurgical patients present to hospital outside regular working hours. The objective of our study was to evaluate the structure of neurosurgical on-call services in Germany, the use of modern communication devices and teleradiology services, and the personal acceptance of modern technologies by neurosurgeons.Materials and Methods A nationwide survey of all 141 neurosurgical departments in Germany was performed. The questionnaire consisted of two parts: one for neurosurgical departments and one for individual neurosurgeons. The questionnaire, available online and mailed in paper form, included 21 questions about on-call service structure; the availability and use of communication devices, teleradiology services, and other information services; and neurosurgeons' personal acceptance of modern technologies.Results The questionnaire return rate from departments was 63.1% (89/141), whereas 187 individual neurosurgeons responded. For 57.3% of departments, teleradiology services were available and were frequently used by 62.2% of neurosurgeons. A further 23.6% of departments described using smartphone screenshots of computed tomography (CT) images transmitted by multimedia messaging service (MMS), and 8.6% of images were described as sent by unencrypted email. Although 47.0% of neurosurgeons reported owning a smartphone, only 1.1% used their phone for on-call image communication.Conclusion Teleradiology services were observed to be widely used by on-call neurosurgeons in Germany. Nevertheless, a significant number of departments appear to use outdated techniques or techniques that leave patient data unprotected. On-call neurosurgeons in Germany report a willingness to adopt more modern approaches, utilizing readily available smartphones or tablet technology.
Keywords: on-call services; teleradiology; smartphone